072 Impact of telehealth on multiple sclerosis (MS) outpatient clinics during the COVID-19 pandemic. (23rd August 2021) - Li, Vivien; Nguyen, Ai-Lan; Roos, Izanne; Buzzard, Katherine; Dwyer, Chris; Marriott, Mark; Monif, Mastura; Malpas, Charles; Roberts, Stefanie; Taylor, Lisa; Carle, Elizabeth; Taylor, Nicola; et al.
Abstract : Objectives: Characterise telehealth use in MS clinics during the COVID–19 pandemic. Assess patient and clinician attitudes towards telehealth. Compare telehealth–based and physical EDSS obtained during period of telehealth implementation. Methods: Clinic records from Mar-Dec 2020 were reviewed. Patients and clinicians completed questionnaires about experiences using Telehealth. The iMed database was searched for EDSS recorded via face-to-face and telehealth appointments during and compared to face-to-face EDSS preceding and following the study period. T-test and Chi-square test were used for between-group comparisons. Results: 2023 appointments (27% face-to-face, 35% video, 37% telephone) were conducted. New referrals were predominantly face-to-face (66%). 89% of patients were satisfied with telehealth. 58% felt they were as good as face-to-face visits, whilst only 11% of clinicians agreed. Many patients favoured a hybrid model. Safety during the COVID-19 pandemic was important to both groups. EDSS increase from the preceding visit was recorded in a significantly higher proportion of face-to-face than telehealth appointments (p=0.027), with the increase driven by patients with baseline EDSS≤4.0. Amongst patients with EDSS increases, similar numbers of suspected relapses were seen via both modalities. Absolute increase in EDSS was also significantly greater amongst patients seen face-to-face (p<0.0001). There was no significant difference in EDSS change at subsequent follow-up in patients with consecutive face-to-face versus intervening telehealth appointments. Conclusion: Patient satisfaction with telehealth was high, whilst clinicians preferred face-to-face consultations. EDSS increase was more frequently recorded via face-to-face than telehealth appointments, which may underestimate lower EDSS. Future clinics could combine both modalities.